Molecularly Imprinted Polymer Coated Quantum Dots for Multiplexed Cell Targeting and Imaging. (30th May 2016) - Panagiotopoulou, Maria; Salinas, Yolanda; Beyazit, Selim; Kunath, Stephanie; Duma, Luminita; Prost, Elise; Mayes, Andrew G.; Resmini, Marina; Tse Sum Bui, Bernadette; Haupt, Karsten
Abstract: Advanced tools for cell imaging are of great interest for the detection, localization, and quantification of molecular biomarkers of cancer or infection. We describe a novel photopolymerization method to coat quantum dots (QDs) with polymer shells, in particular, molecularly imprinted polymers (MIPs), by using the visible light emitted from QDs excited by UV light. Fluorescent core–shell particles specifically recognizing glucuronic acid (GlcA) or N ‐acetylneuraminic acid (NANA) were prepared. Simultaneous multiplexed labeling of human keratinocytes with green QDs conjugated with MIP‐GlcA and red QDs conjugated with MIP‐NANA was demonstrated by fluorescence imaging. The specificity of binding was verified with a non‐imprinted control polymer and by enzymatic cleavage of the terminal GlcA and NANA moieties. The coating strategy is potentially a generic method for the functionalization of QDs to address a much wider range of biocompatibility and biorecognition issues.